2021
DOI: 10.3390/pharmaceutics13020215
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Propolis Combined with 2-Phenoxyethanol and Antipyretics on the Growth of Staphylococcus aureus

Abstract: The present investigation aimed to assess the combinational effect of commonly used antipyretics and antiseptics with ethanolic extracts of propolis (EEPs) on the growth inhibition of Staphylococcus aureus. The broth microdilution checkerboard assay revealed synergistic interactions between all investigated antipyretics, namely acetylsalicylic acid, ibuprofen, and acetaminophen, with EEPs samples. The values of the fractional inhibitory concentration (ΣFIC) index for all these combinations were <0.5. While,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 60 publications
(61 reference statements)
1
1
0
1
Order By: Relevance
“…Presence of phenolic compounds and flavonoides are recognized for antimicrobial activity of propolis [112], Furthermore, phenylates flavonoids, is responsible for cell membrane damage, caused by lipophilic prenyl group. Synergistic activity between phenolic and other compounds was reported previously, by Castaldo [113] and recently, by Grecka [114]. Substances identified in propolis, such as pinocembrin, galangin, caffeic acid, ferulic acid, pinobanksin, benzyl ester, may act on the microbial membrane or cell wall site, causing functional and structural damages [19,105], constituents of propolis can interact with bacterial stucture by forming intramolecular hydrogen bonds that create hydrophobic interactions between the cell wall or membrane and propolis antimicrobial compounds [108].…”
Section: Antibacterial Activitysupporting
confidence: 60%
“…Presence of phenolic compounds and flavonoides are recognized for antimicrobial activity of propolis [112], Furthermore, phenylates flavonoids, is responsible for cell membrane damage, caused by lipophilic prenyl group. Synergistic activity between phenolic and other compounds was reported previously, by Castaldo [113] and recently, by Grecka [114]. Substances identified in propolis, such as pinocembrin, galangin, caffeic acid, ferulic acid, pinobanksin, benzyl ester, may act on the microbial membrane or cell wall site, causing functional and structural damages [19,105], constituents of propolis can interact with bacterial stucture by forming intramolecular hydrogen bonds that create hydrophobic interactions between the cell wall or membrane and propolis antimicrobial compounds [108].…”
Section: Antibacterial Activitysupporting
confidence: 60%
“…Además, existen otras líneas de investigación que trabajan con otro compuesto natural, el própolis, el cual se ha observado que interfiere en la actividad antimicrobiana de algunos antisépticos, aumentándola en el caso de administrarse junto a dihidrocloruro de octenidina (tensioactivo catiónico) o 2-fenoxietanol y disminuyéndola en el caso de la clorhexidina. Estos estudios se encuentran en fase de desarrollo con previsiones a futuras optimizaciones para su uso en la clínica (76) .…”
Section: Poliuretanosunclassified
“…Propolis has a vast number of Chemical Compounds, many of the researchers claimed to have 350 to 500 Chemical Constituents in "Bee Propolis" 3,6,7 . a lot of chemical constituents make Propolis an important topic of research, and the main chemical compounds found in different samples of "Bee Propolis" are: - Galangin 3,6,7,13  Pinocembrin 3,6,7,11,13  Pinobanksin 1,3,13,16  Quercetin 3,10,11,13,14  Apigenin 1,3,11,13  Caffeic Acid 3,14 So, in the formulation development. The Propolis is used as a natural polymer, and HPMC K 200 M is used as a synthetic polymer, and the excipients, such as Lactose, PVP K30, Talc, and Magnesium Stearate are used.…”
mentioning
confidence: 99%